PERLINDUNGAN HUKUM BAGI DEBITUR TERHADAP PENARIKAN PAKSA OBJEK JAMINAN FIDUSIA OLEH DEBT COLLECTOR - Septiana Nurul Hikmah (2022)
The need for transportation for mobility and for supporting the needs of human life is increasing day by day. Meanwhile, the purchasing power of the Indonesian people to buy in cash is quite low, so taking credit is the best solution to able to purchase a private vehicle. Fiduciary Security is the right concerning moving tangible, intangible, and immovable objects that cannot be encumbered with a mortgage and become the most favored security by the people of Indonesia. The fast, easy process and low down payment are supporting factors for the Indonesian people to purchase motor vehicles using the credit payment method. However, quite a lot of debtors are in default, requiring the leasing company to withdraw the debtor's vehicle. The execution of the object of fiduciary security carried out by the leasing company using the services of a debt collector often does not comply with the rules and causes losses to the debtor. So that debtors require legal protection to protect them from forced withdrawals by debt collectors. This study aims to determine the legal use of debt collector agencies and their form of legal protection against debtors for the forced withdrawal of fiduciary objects by debt collectors. The method used in this research is normative legal research based on a statutory approach and examines the literature related to these problems. The legal source of the use of debt collector services in Indonesia is Peraturan Otoritas Jasa Keuangan No. 35/POJK.05/2018 concerning Financing Company Business Operations. However, the regulation does not regulate in detail the limitations of debt collectors' actions in the execution process. This issue requires regulatory reforms to ensure legal certainty for the debtors to get legal protection from the arbitrary actions of debt collectors.